Legal Frameworks for Consumer Protection in Digital Sharia Banking: A Comparative Study between Indonesia and Malaysia - Khasanah, Karimatul; Mohd Salleh, Mohd Mahyeddin (El-Qist: Journal of Islamic Economics and Business (JIEB), 2025)
This study aims to provide a comparative legal analysis of consumer protection frameworks in digital Sharia banking in Indonesia and Malaysia—two countries at the forefront of Islamic financial innovation in Southeast Asia. Employing a normative-comparative legal method, the research examines regulatory structures, Sharia supervisory mechanisms, personal data protection, dispute resolution, and financial literacy provisions. The findings reveal that Malaysia’s centralized and integrated model, led by Bank Negara Malaysia and the Shariah Advisory Council, offers a more coherent and enforceable framework. In contrast, Indonesia's fragmented regulatory landscape—split between OJK and Bank Indonesia—presents challenges in institutional coordination and regulatory consistency. The study highlights how regulatory convergence in Sharia principles is tempered by divergence in enforcement and digital risk governance. By elucidating these legal asymmetries, the article contributes to global Islamic finance literature through actionable insights for cross-jurisdictional harmonization, particularly in Muslim-majority contexts. It recommends the development of hybrid regulatory models that integrate centralized authority with robust Sharia oversight and consumer protection mandates. Future research should extend beyond doctrinal analysis by incorporating empirical stakeholder data and exploring multilateral regulatory convergence at the ASEAN level.